Screening of antibiotics to obtain axenic cell cultures of a marine microalga Chrysotila roscoffensis - Liu, Jiaojiao; Sun, Yan; Zhang, Lin; Li, Xiaohui; He, Zhichao; Zhou, Chengxu; Han, Jichang (Frontiers in Bioengineering and Biotechnology, 2023)
Due to high growth rate, outstanding abiotic stress tolerance, and rich value-added substances, Chrysotila roscoffensis, belonging to the phylum of Haptophyta, can be considered as a versatile resource for industrial exploitation of bioactive compounds. However, the application potential of C. roscoffensis has drawn attention until just recently, and the understanding related to the biological properties of this species is still scarce. For example, the sensitivities of C. roscoffensis to antibiotics, which is essential for the verification of heterotrophic capacity and the establishment of efficient genetic manipulation system is still unavailable. Aiming to provide fundamental information for future exploitation, the sensitivities of C. roscoffensis to nine types of antibiotics were tested in this study. The results demonstrated that C. roscoffensis exhibited relatively high resistances to ampicillin, kanamycin, streptomycin, gentamicin, and geneticin, while was sensitive to bleomycin, hygromycin B, paromomycin, and chloramphenicol. Using the former five types of antibiotics, a bacteria removal strategy was established tentatively. Finally, the axenicity of treated C. roscoffensis was confirmed based on a multi-strategy method including solid plate, 16S rDNA amplification, and nuclear acid staining. This report can provide valuable information for the development of optimal selection markers, which are meaningful for more extensive transgenic studies in C. roscoffensis. Moreover, our study also paves the way for the establishment of heterotrophic/mixotrophic cultivation modes of C. roscoffensis.